SYNCHRONIC RECEPTION OF ERNEST HEMINGWAY’S SELECTED SHORT STORIES (A READER RESPONSE APPROACH) - Maria Fradesanti; Fety Surfaifel; Febe F I Wanggai; Marianus W Liru; Maksimilianus Doi (Lantern: Journal of Language and Literature, 2026)
This study, titled "Synchronic Reception of Ernest Hemingway’s Selected Short Stories (A Reader Response Approach)," examines the interpretations of contemporary readers regarding classic literary works. The primary objective is to analyze how modern readers interpret three selected short stories by Ernest Hemingway: "Hills Like White Elephants," "Cat in the Rain," and "A Clean, Well-Lighted Place." Utilizing Hans Robert Jauss's Reader-Reception Theory, this study focuses on the influence of the horizon of expectations encompassing both aesthetic and non-aesthetic aspects in shaping subjective interpretations. This study employs a synchronic approach through a descriptive qualitative method, involving 25 fourth-semester students of the English Literature Study Program at the University of Flores as respondents. Synchronic reception is defined as an approach in literary studies that analyzes how a literary work is received, interpreted, and appreciated by readers within the same time period. The results reveal that aesthetic aspects, particularly Hemingway’s minimalist style and the "Iceberg Theory," effectively challenge readers to engage actively in dissecting implied meanings. Universal themes such as profound loneliness, moral dilemmas, and the search for love remain highly relevant to modern readers. Furthermore, non-aesthetic aspects, including personal experiences, emotional conditions, and literary literacy levels, significantly shape the unique understanding and appreciation of the texts. Overall, the dynamic interaction between text structure and the readers' sociocultural backgrounds creates a profound reading experience. This demonstrates that the reception of Hemingway’s literature remains alive and continues to evolve dynamically in the current era, transcending the boundaries of generations and time.